Voices, signs, and symbols: Strategies for effective English learning among students with special needs - Ida Ismiyati; Imroatul Ma’fiyah (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2026)
This study explores the communication strategies employed in English language learning for students with special needs (CWSN) at SLB ABCD Tunas Pembangunan 2. Using a descriptive qualitative approach, data were collected through classroom observations, in-depth interviews, and conversation analyses. The research identifies the use of multimodal strategies, echolalia, code-switching, code-mixing, sign language, real-object visualization, and kinesthetic activities as crucial for facilitating vocabulary comprehension and active participation among diverse CWSN groups, including students with intellectual disabilities, hearing impairments, ADHD, and ASD. Findings reveal that integrating these strategies—rather than their isolated use—enhances understanding, engagement, and inclusivity in the learning process. The study underscores the importance of considering students’ socio-cultural backgrounds, individual needs, and real-life experiences in designing effective pedagogical interventions. It contributes both practically, by offering guidance for teachers and curriculum developers, and theoretically, by expanding insights into multimodal communication as a holistic approach to inclusive education for CWSN.